Small states in international relations - Ingebritsen, Christine (New directions in Scandinavian studies., 2006)
Smaller nations have a special place in the international system, with a striking capacity to defy the expectations of most observers and many prominent theories of international relations. This volume of classic essays highlights the ability of small states to counter power with superior commitment, to rely on tightly knit domestic institutions with a shared "ideology of social partnership," and to set agendas as "norm entrepreneurs." The volume is organized around themes such as how and why small states defy expectations of realist approaches to the study of power; the agenda-setting capacity of smaller powers in international society and in regional governance structures such as the European Union; and how small states and representatives from these societies play the role of norm entrepreneurs in world politics -- from the promotion of sustainable solutions to innovative humanitarian programs and policies. Christine Ingebritsenis associate professor of Scandinavian studies and associate dean of undergraduate education, University of Washington, Seattle. Iver B. Neumannis director of research at the Norwegian Institute of International Affairs, Oslo, Norway. Sieglinde Gstohlis professor of European politics and administration at the College of Europe, Bruges, Belgium. Jessica Beyeris a doctoral candidate at the University of Washington. The other contributors include Annette Baker Fox, Jorri Duursma, Michael Handel, Peter J. Katzenstein, Dan Reiter, Baldur Thorhallsson, and David Vital